2006
DOI: 10.1016/j.jep.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal smokes

Abstract: All through time, humans have used smoke of medicinal plants to cure illness. To the best of our knowledge, the ethnopharmacological aspects of natural products' smoke for therapy and health care have not been studied. Mono- and multi-ingredient herbal and non-herbal remedies administered as smoke from 50 countries across the 5 continents are reviewed. Most of the 265 plant species of mono-ingredient remedies studied belong to Asteraceae (10.6%), followed by Solanaceae (10.2%), Fabaceae (9.8%) and Apiaceae (5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(71 citation statements)
references
References 89 publications
(34 reference statements)
1
69
0
1
Order By: Relevance
“…Parvin et al (2010) reported smoke containing polar phenolic compounds displayed the best antimicrobial activities. The advantages of smoke-based remedies are rapid delivery to the brain, a more efficient absorption by the body and lower costs of production (Mohagheghzadeh et al, 2006). Furthermore, no reported study is available on the antimicrobial properties P. atlantica.…”
Section: S Nº Category Nur (Use Citation) Nt (Nº Of Plants Used) Catmentioning
confidence: 99%
“…Parvin et al (2010) reported smoke containing polar phenolic compounds displayed the best antimicrobial activities. The advantages of smoke-based remedies are rapid delivery to the brain, a more efficient absorption by the body and lower costs of production (Mohagheghzadeh et al, 2006). Furthermore, no reported study is available on the antimicrobial properties P. atlantica.…”
Section: S Nº Category Nur (Use Citation) Nt (Nº Of Plants Used) Catmentioning
confidence: 99%
“…The use of cigarettes composed of a mixture of two or more plants to treat neurological disorders is common in some countries (Mohagheghzadeh et al, 2006). The mixture of several plants, which is the usual practice in Asian traditional medicine, brings some advantages, such as the use of low doses of each plant, decreasing the possibility of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…by smoke, which is the popular form of use of 'Tira-capeta' by Quilombolas. The advantages of smoke-based remedies are the rapid delivery to and more efficient absorption of active principles into the brain (Rang et al, 2004;Mohagheghzadeh et al, 2006), justifying the rapid effect reported by the users, which is, in general, limited to the time spent smoking the cigarette. It is worth mentioning that oral administration, as used in the present study, induced stimulatory effects such as seizure in a short time.…”
Section: Catalepsy Testmentioning
confidence: 99%
“…A plethora of research has been published, very recently, and I cite just a few here to provide some scope on the richness of information available for study [72][73][74][75][76][77][78][79][80][81][82][83][84]. Make no mistake that some of the studies cited are motivated by economics and proiteering, as the planet is scoured for 'new' plant materials that can become the 'next' food, nutraceutical, medicine or biotechnology product.…”
Section: Ethnobotany Traditional Use and The Search For Resilient Grmentioning
confidence: 99%